2019
DOI: 10.1186/s12981-019-0239-x
|View full text |Cite
|
Sign up to set email alerts
|

HIV-2 as a model to identify a functional HIV cure

Abstract: Two HIV virus types exist: HIV-1 is pandemic and aggressive, whereas HIV-2 is confined mainly to West Africa and less pathogenic. Despite the fact that it has been almost 40 years since the discovery of AIDS, there is still no cure or vaccine against HIV. Consequently, the concepts of functional vaccines and cures that aim to limit HIV disease progression and spread by persistent control of viral replication without life-long treatment have been suggested as more feasible options to control the HIV pandemic. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 160 publications
(147 reference statements)
0
26
0
Order By: Relevance
“…Tscm cells are a small subset of T cells possessing self-renewal capabilities, that when stimulated via the T cell receptor, may divide into mature memory or effector T cells (49,51). Many studies have consistently reported a close and robust association between the proliferation of effector cells and memory T cells and virus control in HIV infection (1,2,52). However, there is a lack of clarity in this line with regard to HIV-2 infection due to the limited number of studies in HIV-2 individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tscm cells are a small subset of T cells possessing self-renewal capabilities, that when stimulated via the T cell receptor, may divide into mature memory or effector T cells (49,51). Many studies have consistently reported a close and robust association between the proliferation of effector cells and memory T cells and virus control in HIV infection (1,2,52). However, there is a lack of clarity in this line with regard to HIV-2 infection due to the limited number of studies in HIV-2 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired immunodeficiency in humans is caused by two types of human immunodeficiency virus (HIV), namely HIV-1 and HIV-2 (1). HIV-2 is less pathogenic than HIV-1, the course of disease is slower, and the proportion of disease controllers is significantly greater with HIV-2 infection (2).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a patient who was infected with a vpr-defective HIV-1 molecular clone and became an EC has been described [8] and members of a transmission cluster of ECs have been found to be infected with HIV-1 isolates that contain related attenuated env genes [9] . Furthermore, the high percentage of people living with HIV-2 who become controllers suggests that viral factors may play a role in clinical outcomes [10] . Taken together, such studies suggest that infection with attenuated or defective viruses can lead to elite control, but they do not indicate that all ECs are infected with defective virus.…”
Section: Evidence Of Replication-competent Virus In Ecsmentioning
confidence: 99%
“…Both viruses share comparable genetic organization, structural architecture, and most virological features. Despite this close relationship, the clinical progression of HIV-2 to AIDS is much slower compared to HIV-1 and may reflect better immune control of the infection ( Marlink et al, 1994 ; Nyamweya et al, 2013 ; Esbjörnsson et al, 2019 ). A much larger proportion of people with HIV-2 infection exhibit long-term viral control without ART than is seen in HIV-1 infection ( van der Loeff et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although, it is estimated that 30–40% of HIV-2 infected people have low or undetectable viral loads ( van der Loeff et al, 2010 ), ongoing viral replication still occurs in HIV-2-infected patients ( Soares et al, 2011 ; Fernandes et al, 2014 ). However, a recent longitudinal study indicates that without ART treatment, HIV-2-infected individuals have still a high probability of developing and dying from AIDS despite the longer time to progress ( Esbjörnsson et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%